Easy entertaining at home - Lee, Sandra, 1966- (New York : Hyperion, 2011)
"In this new book, Sandra Lee shows you how to throw a party or informal gathering for friends for any and every occasion - all year round. This perfect party primer will be the ultimate resource and go to guide for modern, over-extended homemaker's and shoppers who entertain on an average of 6 times a year. Going from January to December, with fabulous, themed cocktails, delicious, easy to prepare canapš, and inventive decorations, this richly illustrated book will make home entertainment fast, fun and stress free"--
Includes index.
Cocktails, finger foods, and creative ideas for year-round celebrations--Cover.
Keywords: Entertaining; Beverages; Cookbooks